Modification of jet shapes in PbPb collisions at √sNN = 2.76 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (Elsevier, 2014)
The first measurement of jet shapes, defined as the fractional transverse momentum radial distribution, for inclusive jets produced in heavy-ion collisions is presented. Data samples of PbPb and pp collisions, corresponding to integrated luminosities of 150 μb-1 and 5.3 pb-1 respectively, were collected at a nucleon-nucleon centre-of-mass energy of sNN=2.76TeV with the CMS detector at the LHC. The jets are reconstructed with the anti-kT algorithm with a distance parameter R = 0.3, and the jet shapes are measured for charged particles with transverse momentum pT > 1GeV/c. The jet shapes measured in PbPb collisions in different collision centralities are compared to reference distributions based on the pp data. A centrality-dependent modification of the jet shapes is observed in the more central PbPb collisions, indicating a redistribution of the energy inside the jet cone. This measurement provides information about the parton shower mechanism in the hot and dense medium produced in heavy-ion collisions. © 2014 The Authors.